2013
DOI: 10.1063/1.4816439
|View full text |Cite
|
Sign up to set email alerts
|

Transport through a single donor in p-type silicon

Abstract: Single phosphorus donors in silicon are promising candidates as qubits in the solid state. Here, we present low temperature scanning probe microscopy and spectroscopy measurements of individual phosphorus dopants deliberately placed in p-type silicon $1 nm below the surface. The ability to image individual dopants combined with scanning tunnelling spectroscopy allows us to directly study the transport mechanism through the donor. We show that for a single P donor, transport is dominated by a minority carrier r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Samples with P donors were fabricated by submonolayer PH 3 dosing and well-defined encapsulation by epitaxial silicon, using a procedure similar to the one in Ref. [10], but with an n-type substrate to promote elastic resonant transport [4,11]. Experiments on the donors were carried out with atomic resolution in real space, in the single-electron transport regime with both the tip and a heavily-doped region of the sample, at liquid Helium temperatures, acting as transport reservoirs [12].…”
Section: Real Space Resultsmentioning
confidence: 99%
“…Samples with P donors were fabricated by submonolayer PH 3 dosing and well-defined encapsulation by epitaxial silicon, using a procedure similar to the one in Ref. [10], but with an n-type substrate to promote elastic resonant transport [4,11]. Experiments on the donors were carried out with atomic resolution in real space, in the single-electron transport regime with both the tip and a heavily-doped region of the sample, at liquid Helium temperatures, acting as transport reservoirs [12].…”
Section: Real Space Resultsmentioning
confidence: 99%
“…The P dopants were incorporated in Si by PH 3 dosing. A low P density was overgrown with 2.5 nm of Si by in-situ epitaxy 17 (i.e. a target depth of 4.75a 0 , where a 0 = 0.5431 nm is the Si lattice constant).…”
Section: Stm Measurement Of Dopant Statementioning
confidence: 99%
“…12 Consequently, As dopants measured in these samples were found at random depths in a ∼10 nm thin thermally depleted Si layer below the surface. Samples with P dopants were prepared by incorporating P in Si by a sub-monolayer phosphine (PH 3 ) dosing of the previously flash annealed Si substrate 17 . A sheet density of 5 × 10 11 cm −2 P donors is overgrown epitaxially by ∼2.5 nm (4.75a 0 , where a 0 is Si lattice constant) of Si.…”
Section: S1 Experimental Proceduresmentioning
confidence: 99%
“…These studies have revealed the influence of the semiconductor/vacuum interface on the ionization energy of sub-surface dopants [9,13], the spatially resolved structure of the dopant wavefunction [10][11][12] and the mechanisms for charge-transport through these dopants [9,11,14]. Here, we use STS to measure the energy difference between the heavy-hole and light-hole states of individual B acceptors less than 2 nm away from the surface.…”
mentioning
confidence: 99%